Reflections on Progress Essays on the Global Political Economy - Dervis, Kemal (Brookings Institution Press, 2016)
Now, more than ever, the world needs growth-oriented and socially inclusive policymaking. Is the world giving up on the promise of ever-greater prosperity for all, on functioning democratic institutions, and on long-term peace? Is the special set of circumstances that led to the recent rapid growth in emerging markets unlikely to be present in the future? Will the second decade of the twenty first century end with secular stagnation"? Does the rise of authoritarianism, populism, and fanatic nihilismall experienced over the last few yearsthreaten to unravel what has been built painstakingly since the catastrophe of World War II? Kemal Dervis addresses these and similar questions in this thought-provoking series of essays written for Project Syndicate from 2011 to 2015. The essays are organized in three sections: global economic interdependence, inequality and the political economy of reform, and the specific challenge of Europe. The common theme is the need for growth-oriented and socially inclusive policymaking in an interdependent world. These kinds of policies offer the potential for another wave of unprecedented human progress aided by breathtaking new technologies. However, a huge and destabilizing disruption is possible if policymaking is not globally cooperative and is not focused on inclusion and greater equity. These essays synthesize the experience and analysis of a scholar and policymaker with national, regional, and international experience at the highest levels. Dervis exhibits a passion for combining strongly held values with political feasibility